Pengelolaan Hyigiene Dan Sanitasi Lingkungan Pada Objek Wisata Pemandian Air Soda Tarutung - Apriliana Lase; Jessica Ignatia Tambunan; Apriliani Lase; Fitri Irda Notalya Gulo (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Aspects of environmental sanitation and hygiene at the Soda Water Bath tourism object still do not meet operational standards in terms of the environment of the tourist attraction, food and drink and there is a lack of knowledge about environmental hygiene and sanitation at the tourist attraction. This research aims to obtain an overview of the implementation of sanitation facilities in public baths in the Tarutung Soda Water Baths tourist attraction area. The research method used is descriptive with a qualitative approach. Data collection techniques include observation, in-depth interviews, and documentation with data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The results of this research indicate that the management of sanitation facilities at the Tarutung soda water baths is still very poor and needs improvement to ensure environmental cleanliness. The environmental sanitation management techniques implemented by the management start from inadequate planning and maintenance, lack of provision of rubbish bins in the tourist area, lack of cleanliness in the bathroom area resulting in an unpleasant odor in the area near the bath, lack of a special room for changing clothes. for tourists, as well as food sanitation that still does not meet standard food sanitation requirements. The author hopes that the management of the Soda Water Baths tourist attraction can improve the condition of the tourist attraction's sanitation facilities, so that paying attention to cleanliness will create comfort for visitors, because the better the sanitation facilities at a tourist attraction, the higher the level of comfort for tourists.